Public Relations As Political Communication In The 2024 DPD Campaign Of Mamberob Rumakiek - Wiryawan Kresna Wisnu Brata; Tria Patrianti; Ismed Kelibay; Tito Handoko (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study examines the role of political public relations in building political relations and public communication of Mamberob Yosephus Rumakiek in the election of the Regional Representative Council of the Republic of Indonesia. The analysis focuses on two main aspects: (1) the formulation of political messages and public responses to these messages, and (2) patterns of two-way communication and political representation constructed by Kaka Mambe. This study employs the theoretical framework of political public relations proposed by Frohlich. A descriptive qualitative method is applied, with the research conducted at the DPD RI office and within Kaka Mambe’s constituency in Southwest Papua. Data were collected through in-depth interviews with Kaka Mambe as the key informant, as well as Papuan community leaders, campaign team members, youth activists, and Papuan academics as supporting informants. Data analysis was carried out using comparative context and analogy approaches, and data validity was ensured through triangulation to establish research credibility and dependability. The findings indicate that the political PR strategy implemented by Kaka Mambe, through contextual political messaging, responsive two-way communication, and political representation grounded in local values, has proven effective in building political relations and strengthening political communication, thereby contributing significantly to his success in the DPD RI election.